2016
DOI: 10.1186/s40064-016-2230-5
|View full text |Cite
|
Sign up to set email alerts
|

The optimal reconstruction size of nipple-areola complex following breast implant in breast cancer patients

Abstract: BackgroundChanges in the areola size after reconstruction of the nipple-areola complex (NAC) following mastectomy and breast reconstruction with a silicon implant in primary breast cancer patients have not been well examined. This study aimed to investigate time-dependent changes in the size of the donor and graft NACs and to assess clinical factors influencing these changes.MethodsFifty-eight consecutive patients who underwent nipple-areola reconstruction were retrospectively evaluated. Nipple-areola diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…If darker, suitable donor sites include the labia minora and majora from the groin [ 16 , 17 ], the buttock [ 18 ] or the upper thigh [ 19 ], because skin harvested from these areas supposedly tends to hyperpigment [ 6 ]. Some propose harvesting the outer rim of the contralateral areola, which can be useful in patients with large NAC who would simultaneously benefit from an areolar reduction [ 20 ]. If no donor site is available, Seaman proposes using an acellular dermal matrix (Alloderm) as an onlay graft [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…If darker, suitable donor sites include the labia minora and majora from the groin [ 16 , 17 ], the buttock [ 18 ] or the upper thigh [ 19 ], because skin harvested from these areas supposedly tends to hyperpigment [ 6 ]. Some propose harvesting the outer rim of the contralateral areola, which can be useful in patients with large NAC who would simultaneously benefit from an areolar reduction [ 20 ]. If no donor site is available, Seaman proposes using an acellular dermal matrix (Alloderm) as an onlay graft [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Such surgery commonly involves relocation of the nipple-areola complex, with a focus on the esthetic appearance of its location post-surgery [1][2][3][4]. Several studies have further sought to preserve nipple prominence [5][6][7][8][9], some of which have involved novel suturing techniques aimed at enhancing nipple prominence. The majority of studies have been based on relatively few patients (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Areola reconstruction is often performed by grafting from the upper inner thigh or contralateral areola or alternatively by intradermal paramedical pigmentation [38]. In order to provide a color and produce a more realistic appearance,several authors reported that tattooing is the ideal technique among the areola reconstruction procedures [39 -41].…”
Section: Introductionmentioning
confidence: 99%